Financial conditions indicator for Brazil - Wagner Piazza Gaglianone; Waldyr Dutra Areosa (Inter-American Development Bank (IDB), 2017)
This paper proposes a methodology for constructing a Financial Conditions Indicator (FCI) based on factor analysis and the approaches of Brave and Butters (2011) and Aramonte et al. (2013). A selected set of variables is used and their information content aggregated into a single index that summarizes the overall financial conditions of the economy. The approach is further employed to forecast economic activity. An empirical exercise for Brazil is provided to illustrate the methodology, in which a reduced-form equation is employed to point forecast the growth rate of the Brazilian economy. In addition, a quantile regression technique is used to construct density forecasts and generate probability density functions of future economic activity. Finally, a risk analysis is conducted within this set-up in order to compute conditional probabilities of the growth rate of the economy to be above/below a given scenario, which might be useful for both academics and policymakers' concerns.
hdl:11319/8488
Keywords: C53; E32; G10; G17; 330; Financial conditions index; Forecasting economic activity